2016
DOI: 10.1111/cod.12603
|View full text |Cite
|
Sign up to set email alerts
|

Skin health and safety at work in Croatian hairdressing apprentices

Abstract: The results indicate the need for the continuation of efforts to establish effective primary preventive programmes for OSDs at national and EU levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 31 publications
5
51
0
1
Order By: Relevance
“…The results of a previous study on Croatian hairdressing apprentices at the end of their training confirmed high exposure to skin hazards during vocational education, as has also been found in other studies, particularly in terms of hair washing and dyeing, and rinsing dye from the hair. Poor skin protection habits of Croatian hairdressing apprentices, and probably poor supervision of their vocational teachers and tutors regarding prevention of the irritant effects of wet work on skin, was suspected.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…The results of a previous study on Croatian hairdressing apprentices at the end of their training confirmed high exposure to skin hazards during vocational education, as has also been found in other studies, particularly in terms of hair washing and dyeing, and rinsing dye from the hair. Poor skin protection habits of Croatian hairdressing apprentices, and probably poor supervision of their vocational teachers and tutors regarding prevention of the irritant effects of wet work on skin, was suspected.…”
Section: Introductionsupporting
confidence: 81%
“…Apprentices from both regions were examined: those from Zagreb from 21 April to 6 May 2015, and those from Dalmatia from 2 to 4 May 2016. The study protocol and recruitment process were the same as described previously . Briefly, the participants were invited to participate in the study via a presentation and flyers at school.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations